The Principal's Policy in Developing Bilingualism at the As-Sunniyyah Darungan Yosowilangun Leading Madrasah - Siti Muthiatun Najiyah; Siti Aminah; Diah Ainun Khafidloh; Titin Nurhidayati (Penerbit Hellow Pustaka, 2026)
This study aims to analyze the policies of the madrasah principal in developing a bilingual program at Madrasah Ibtidaiyah Program Unggulan As-Sunniyyah Darungan. The development of bilingual education has become one of the strategies to improve the quality of education by emphasizing mastery of Indonesian, Arabic, English, and regional languages (Krama Inggil). This study employed a qualitative approach using a case study design. The findings reveal that the madrasah principal’s policies include program planning, strengthening teachers’ competencies, language habituation, and continuous evaluation. The bilingual program has a positive impact on improving students’ language skills and enhancing the competitiveness of the madrasah.